Trocas gasosas e qualidade dos frutos de meloeiro amarelo cultivado em diferentes temperaturas - Pontes, Cibele Araújo (2014)
In recent years the increase in greenhouse gases, has increased the temperature of the earth. Given the economic importance of melon crop, there is a need to study how temperature effects act on the rates of gas exchange and quality of these plants. Currently, it can not be inferred the competitiveness of melon production systems without conducting research on the impacts of this climate change on culture. The experiment was conducted and the experimental area of Embrapa, in the city of Pacajus-Ceará, with the aim of studying post-harvest fruit quality of yellow melon "Goldex", aimed at adapting this culture to high temperature conditions. Yellow melon "Goldex" was grown under field conditions in the period July to September 2013 in order to collect temperature data measured by sensors (DataLogger) and gas exchange measurements through the IRGA, in which the collections were performed once a week. One group of plants was conducted in accordance with the commercial production system already used in the producing states, with the same irrigation schedules, fertilization and phytosanitary treatment (control treatment), another group was conducted under shaded area (chamber) chapel plastic type, which is expected an increase in temperature around 2 ° C, forming a sort of microclimate. The experiment was conducted in factorial outlining randomized block, which treatments were two rooms (with chamber and without chamber), three storage periods (0, 14 and 21 days), four blocks. For the analysis of gas exchange the least significant difference for the comparison of treatments was used. The use of chambers provided an average increase of 2 ° C temperature. There was a significant influence of the environment on the physical length and diameter of the internal cavity and firmness of the stern, which the rise in temperature reduced the internal cavity of the fruit, making them firmer. Regarding the physical and chemical characteristics was no significant influence of the environment on vitamin C, soluble solids and titratable acidity, yet the quality of the fruit was little influenced by temperature and gas exchange were not affected by temperature